(untitled) (Research, Society and Development, 2022)
Knowing the importance and relevance that drawing an epidemiological profile brings in the fight against mortality and guide the decision-making of actions, this final paper mapped the number of hospitalizations and deaths from pneumonia, seeking to identify which gender, ethnicity and age group most affected in Alagoas. This is a retrospective, cross-sectional study listed on data from pneumonia notifications in the state of Alagoas, cases reported between 2008 and 2019, made available by the Hospital Information System (SIH/SUS), were analyzed by Department of Informatics of the Unified Health System (DATASUS), consulted in June 2021. It wasn’t necessary to submit the final paper to the ethics committee, cause it’s a source of public control. It was observed that there is a predominance of inmates in Alagoas for males, browns and children aged nine years or less. The analysis of the epidemiological p allowed us to guarantee that extreme ages, which are the most vulnerable, suc children and the elderly, are characterized as the profile that are most affected and that most die, respectively.